Three‐Dimensional Magnetic Models of La Gomera (Canary Islands): Insights Into the Early Evolution of an Ocean Island Volcano. (18th February 2020) - Blanco‐Montenegro, I.; Montesinos, F. G.; Nicolosi, I.; Arnoso, J.; Chiappini, M.
Abstract: An aeromagnetic data set from the island of La Gomera was studied through two inverse modeling approaches that produced complementary views of the inner structure of this volcanic island: (1) a variable magnetization model that identified the main lateral magnetization contrasts and (2) a constant magnetization model that imaged the main magnetic source by assuming that it was a uniformly magnetized body. The modeling reveals intense magnetizations beneath the northern part of La Gomera, which occupy an important portion of the northern submarine edifice, correspond well with outcrops of the submarine volcano (Basal Complex), and confirm that most of the magnetic signal revealed by aeromagnetic mapping in the Canary Islands is due to the intense magnetizations of the intrusive complexes (plutonic bodies and dike complexes) emplaced during the initial stages of growth of the volcanic edifices. The consistency of our models with the results of a previous gravimetric study suggests that these intrusive complexes are denser and more magnetic than the surrounding rocks. The location of the main magnetic source reinforces the interpretation, first suggested by geological evidence, that the submarine and early subaerial growth of La Gomera started to the north of the present island. The elongated shape of these intrusive complexes with a nearly E‐W strike agrees with the orientation of analogous structures on Tenerife and Gran Canaria, suggesting that the initial formation of the central islands of the Canary Archipelago was controlled by a set of regional fractures in a strike‐slip tectonic framework. Plain Language Summary: Airborne magnetic mapping reveals differences in the rocks' magnetizations of buried geological structures. Through the application of inversion algorithms to magnetic anomaly data, three‐dimensional models of the geological structures that are responsible for the measured anomalies can be obtained. In volcanic islands, most anomalies are created by the intrusive structures which formed as a result of the ascent and emplacement of molten magma that did not reach the surface, because when they cooled in the presence of the Earth's magnetic field, they acquired a strong remanent magnetization. The most important intrusive bodies are those emplaced during the early growth of the volcanic island, which occurred under the sea. Our magnetic models from La Gomera reveal that these intrusive bodies are located beneath the northern part of the island, suggesting that the center of the early volcano is under the sea to the north of the present coastline. This result is consistent with previous works based on geological evidence that hypothesized that volcanic activity in La Gomera started to the north and migrated southward in later stages. These intrusive bodies were also imaged by gravity anomaly data in a previous work that identified a dense structure corresponding with the highly magnetic body. Key Points: We obtained three‐dimensional magnetic models of intrusive bodies on La Gomera through inversion of aeromagnetic data The location of the plutonic core of La Gomera indicates that the volcanic submarine growth started to the north of the island The E‐W strike of the main magnetic source suggests a regional tectonic control over the early emplacement of magmas